The Internet Trap: Five Costs of Living Online (getAbstract Summary). - , getAbstract (linkedin.com, 2019)
Caught in the internet trap? Learn about the commercial and social “costs” of living online and how to overcome them in this audio-only review of Ashesh Mukherjee’s book.